2004
DOI: 10.1152/ajplung.00125.2003
|View full text |Cite
|
Sign up to set email alerts
|

Salmeterol, a β2-receptor agonist, attenuates lipopolysaccharide-induced lung inflammation in mice

Abstract: der Poll. Salmeterol, a ␤2-receptor agonist, attenuates lipopolysaccharide-induced lung inflammation in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 42 publications
5
39
1
Order By: Relevance
“…The concept that ␤-adrenoceptor stimulation, whether it was endogenous or exogenous, can reduce lung endothelial permeability has been intermittently supported by a variety of experimental models (17,21,27,28) and one study in human volunteers (20), but the proof of its beneficial effect in an acute model of established severe bacterial pneumonia has not been previously demonstrated. ␤-Adrenoceptor stimulation may improve lung endothelial permeability (17,27,28) by inhibiting endothelial cell contraction and reducing intracellular gaps (19,34).…”
Section: Discussionmentioning
confidence: 99%
“…The concept that ␤-adrenoceptor stimulation, whether it was endogenous or exogenous, can reduce lung endothelial permeability has been intermittently supported by a variety of experimental models (17,21,27,28) and one study in human volunteers (20), but the proof of its beneficial effect in an acute model of established severe bacterial pneumonia has not been previously demonstrated. ␤-Adrenoceptor stimulation may improve lung endothelial permeability (17,27,28) by inhibiting endothelial cell contraction and reducing intracellular gaps (19,34).…”
Section: Discussionmentioning
confidence: 99%
“…This response is rapidly tachyphylactic, reflecting the low density of b 2 -receptors on these cells. In animal models of neutrophilic inflammation, such as lipopolysaccharideinduced lung inflammation in mice, b-agonists have an inhibitory effect on neutrophil recruitment to the lung [48], which may be mediated by an inhibitory effect on the adhesion molecule CD11b on the cell surface [49]. Clinical studies have shown that in patients with mild asthma there is a decrease in neutrophils in bronchial biopsies and bronchoalveolar lavage after treatment with salmeterol, as well as a reduction in myeloperoxidase and human neutrophil lipocalin, indicating an inhibitory effect of neutrophil degranulation [50].…”
Section: Mast Cell Stabilisationmentioning
confidence: 99%
“…In addition to bronchodilation, -agonists may also possess anti-inflammatory activity (Barnes, 2006;Theron et al, 2013). Both in vitro and in vivo studies suggest that -agonists may dampen inflammation although there are inconsistencies (Schild, 1937;O'Connor et al, 1994;Maris et al, 2004, Maris et al, 2005Bosmann et al, 2012;Wex et al, 2015). It is noteworthy that in many of these studies animal models or cell lines have been employed.…”
Section: Introductionmentioning
confidence: 99%